Self-adaptability parallel active filter to load variations study - Derrouazin, Ahmed; Moussa, Mohamed Ali; Mokhtari, Bachir (Institute of Advanced Engineering and Science, 2024)
Due to the increasing use of power electronics equipment, the quality of energy in the electrical network is deteriorating sharply. Indeed, this equipment consumes non-sinusoidal currents, even if they are powered by a sinusoidal voltage, and behaves like generators of harmonic currents. To